Abrupt Cessation of One-Year Clopidogrel Treatment Is Not Associated With Thrombotic Events - Nina Djukanovic; Zoran Todorovic; Slobodan Obradovic; Danijela Zamaklar-Trifunovic; Srdjana Njegomirovic; Nataša M. Milic; Milica Prostran; Miodrag Ostojic (Elsevier, 2011)
Abstract.: We aimed to examine the rate of thrombotic events after discontinuation of one year clopidogrel therapy in patients with implanted coronary stent, and to determine platelet aggregability by multiple electrode analyzer after cessation of clopidogrel. This prospective, multicenter study enrolled 200 patients subjected to coronary stent implantation and treated with aspirin + clopidogrel one year after the stent placement. Platelet aggregation was measured using 3 agonists [adenosine diphosphate with PGE1 (ADPHS), arachidonic-acid (ASPI), and thrombin receptor activating peptide (TRAP)] on the day of cessation of clopidogrel and at 10, 45, and 90 days after clopidogrel was stopped. Two thrombotic events were registered during the 6-months follow up (one ischemic stroke and one myocardial infarction; incidence of 1%). The mean values of ADP + PGE1- and ASPI-induced aggregation 10 - 90 days after the cessation of clopidogrel were significantly higher than values obtained before the termination of the drug (P < 0.001, all). Cessation of clopidogrel did not influence the TRAP-induced aggregation, which reached the plateau in all measurements. In conclusion, the incidence of thrombotic events after the cessation of one-year clopidogrel treatment might be lower than expected in patients with implanted coronary stent. Keywords:: clopidogrel, cessation, rebound effect, thrombotic event